Raba družbenih zvrsti jezika pri pouku slovenščine in širše v osnovnošolskem izobraževanju - Kralj, Tadej (Slavia Centralis, 2025)
Using Social Varieties in Slovenian Language Lessons and Broader in Elementary School Education. Spreading globalization and increasing digitization have affected the linguistic situation in Slovenia regarding languages in contact – both English on the one side and languages of immigrants on the other. Consequently, modern social conditions have blurred students’ perception about situational use of either literary or non-literary varieties of language. The Curriculum for Slovene (2018) is dichotomous, as it mainly introduces students merely to what literary and non-literary language varieties are. School is a key factor in the development of Slovenian language identity, and students must be introduced to the theory of language varieties with examples for everyday speech situations. The purpose of this article is to demonstrate how to raise linguistic consciousness in school practices, i.e. not solely focusing on the attitude towards the literary variety, but also towards regional language types, especially to dialect and slang, which are most often used by students in everyday speech situations.